How bad are e‐cigarettes? What can we learn from animal exposure models?. (26th June 2020) - Marczylo, Tim
Abstract: Electronic cigarettes divide opinions. Some consider them key to reducing smoking incidence while others are concerned over potential for detrimental health consequences. It will take many years to identify the health consequences of e‐cigarette use if we rely only upon human data. However, there is a growing body of work using rodent models that inform on these potential toxicities. These studies have focused upon the pulmonary, cardiovascular and central nervous systems. Observations include perturbations of pro‐inflammatory, pro‐fibrotic and oxidative stress markers, sometimes together with DNA damage and downregulation of DNA repair and antioxidant enzymes. However, the markers affected are often different between studies. A more consistent observation has been the increase in airway hyperresponsiveness, a characteristic of asthma, on exposure to electronic cigarettes, across mouse strains, sex and ages. Detrimental effects in this and other susceptible animal models such as the apolipoprotein E knock‐out mouse model of atherosclerosis, suggest greater risk where there is an existing predisposition. Other adverse reactions, including weight loss, oxidative stress and angiogenesis, are reported in animal studies with nicotine‐containing devices. These effects remain less severe than cigarette smoke, where investigated. Animal studies have identified therefore that e‐cigarettes are potentially hazardous, especially in susceptible populations, nicotine is integral to risk of health effects, but overall e‐cigarettes are much less hazardous than cigarettes. Abstract : Abstract figure legend : Summary of adverse effects observed in animal models following e‐cigarette exposure.